A descriptive analysis of Urali (Speech of a Dravidian Hill Tribe) - Sam Mohan Lal (Central Institute of Indian Languages Mysore, 1991)
The books provides a detailed linguistic analysis of Irula language.
Keywords: Irula; Descriptive Linguistics; English